Microtubule remodeling by the innate immune factor Trim69 compromises dynein-dependent migration of HIV virion cores toward the nucleus - Charlotte Vadon; Xuan-Nhi Nguyen; Valerie Siahaan; Yuxin Song; Arya Krishnan; Veronique Henriot; Amandine Chantharath; Julien Burlaud-Gaillard; Philippe Roingeard; Carsten Janke; Lucie Etienne; Francesca Fiorini; et al. (Proceedings of the National Academy of Sciences, 2025)
Like many viruses, HIV relies on the microtubule (MT) cytoskeleton for successful infection. MT-associated proteins (MAPs) regulate MT functions and thus bear the potential to modulate viral infection. However, while several MAPs are known to exert proviral effects on HIV, little is known about antiviral ones. We previously described the Tripartite motif protein 69 (Trim69) as an innate immune factor that remodels MTs, leading to inhibition of a broad spectrum of viruses, including HIV. Through in silico modeling, TIRF microscopy, and cell-based assays, we determine that Trim69 binding to MTs is determined by a basic surface in its SPRY domain that interacts with the C-terminal tails of tubulins. This surface is conserved among mammalian Trim69s and is critical for its functions. We demonstrate that by binding and remodeling MTs, Trim69 inhibits the docking and the migration of virion cores on MTs by promoting the stalling of the dynein/dynactin motor complexes. Altogether, these findings shed light on a mechanism of viral defense that involves an innate immune regulation of the MT cytoskeleton.